"The outermost of the bedcloaths; that under which all the rest are concealed": A Study of Bedcovers in Eighteenth-century Huntingdonshire. (2nd January 2016) - Long, Bridget
Abstract : This paper examines eighteenth-century consumption practices in a small agricultural county through the lens of a single bedroom textile. Drawing on detail in more than three hundred and seventy Huntingdonshire probate inventories, it considers bedcover ownership in the county of Huntingdonshire over the long eighteenth century and whether the use of one household commodity changed in the period. The study enables a useful comparison with work on bedcovers and bedcover terminology in metropolitan London.